2018
DOI: 10.3390/ijms19092651
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Classification and Anti-Cancer Effects of Plant Metabolites

Abstract: A variety of malignant cancers affect the global human population. Although a wide variety of approaches to cancer treatment have been studied and used clinically (surgery, radiotherapy, chemotherapy, and immunotherapy), the toxic side effects of cancer therapies have a negative impact on patients and impede progress in conquering cancer. Plant metabolites are emerging as new leads for anti-cancer drug development. This review summarizes these plant metabolites with regard to their structures and the types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 193 publications
(247 reference statements)
0
46
0
6
Order By: Relevance
“…Plant extracts are now an important source for our treatment of diseases [26,27],and many countries have invested huge amounts of money in the development of extracts to treat cancer. Paeoni orin is used as an extract of Ranunculaceae, Peony, and Purple Peony [28].The compound structure was showned in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts are now an important source for our treatment of diseases [26,27],and many countries have invested huge amounts of money in the development of extracts to treat cancer. Paeoni orin is used as an extract of Ranunculaceae, Peony, and Purple Peony [28].The compound structure was showned in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds are specifically used to treat tumors in CHM [116]. Several studies revealed that active metabolites among the terpenoids, including carotenoids, polyphenols and alkaloids that can obtained from marine source [117][118][119][120][121][122][123][124][125]. Compounds from natural sources with antiproliferative activity represent an important and novel alternative to treat several types of cancer.…”
Section: Herbal and Non-herbal Plant Derivativesmentioning
confidence: 99%
“…Recently, natural compounds from plants have garnered increasing attention either as potential drugs or lead compounds in drug discovery research [16,17]. The key benefits of natural compounds are the abundance of plants, compound diversity, and cost effectiveness.…”
Section: Introductionmentioning
confidence: 99%